Knowledge about complications and practice of abortion among female undergraduates in the University of Ibadan, Nigeria. (2011)
Background: Unwanted pregnancies and unsafe abortion pose major health risks to women in the reproductive age group. Female undergraduates are particularly exposed to these risks. This study was carried out to assess the knowledge about complications and practice of abortion among female undergraduates of the University of Ibadan. Methods: A cross-sectional study was conducted using structured, self-administered questionnaires, to collect data on respondents’ socio-demographic characteristics, sexual behaviour, knowledge about various complications of abortion and practice of abortion. Data was analyzed using SPSS version 14. Results: A total of 425 students were interviewed, mean age of the undergraduates was 21.5± 2.8 years. Overall, 122 (29%) of the respondents had ever had sexual intercourse. Twenty five percent of those who were sexually active had ever been pregnant and 90% had terminated the pregnancy. The most common reason given for termination was that pregnancy was unplanned for. Most of the respondents 354 (83.3%) had a good knowledge about complications of abortion and mean knowledge score was 4.01±1.58 (range 0-5). Conclusion: This group of students were aware of the risks associated with unsafe abortion; however, the abortion rate was still high. Sexual reproductive health interventions are needed on campus in order to equip female undergraduates with comprehensive knowledge and skills to reduce the likelihood of unplanned pregnancies.